CDKN1B/p27 regulates autophagy via the control of Ragulator and MTOR activity in amino acid-deprived cells. Issue 12 (1st December 2020) - Nowosad, Ada; Besson, Arnaud
ABSTRACT: The tumor suppressor CDKN1B/p27 Kip1 binds to and inhibits cyclin-CDK complexes in the nucleus, inducing cell cycle arrest. However, when in the cytoplasm, CDKN1B may promote tumorigenesis. Notably, cytoplasmic CDKN1B was reported to promote macroautophagy/autophagy in response to nutrient shortage by a previously unknown mechanism. In our recent work, we found that during prolonged amino acid starvation, CDKN1B promotes autophagy via an MTORC1-dependent pathway. A fraction of CDKN1B translocates to lysosomes, where it interacts with the Ragulator subunit LAMTOR1, preventing Ragulator assembly, which is required for MTORC1 activation in response to amino acids. Therefore, CDKN1B represses MTORC1 activity, leading to nuclear translocation of the transcription factor TFEB and activation of lysosomal function, enhancing starvation-induced autophagy flux and apoptosis. In contrast, cells lacking CDKN1B survive starvation despite reduced autophagy, due to elevated MTORC1 activation. These findings reveal that, by directly repressing MTORC1 activity, CDKN1B couples the cell cycle and cell growth machineries during metabolic stress.